The young open cluster NGC 7067 using Strömgren photometry. Issue 3 (17th December 2016) - Monguió, M; Negueruela, I; Marco, A; González-Fernández, C; Alonso-Santiago, J; Costado, M T; Casamiquela, L; López-Corredoira, M; Molgó, J; Vilardell, F; Alfaro, E J; Antoja, T; et al.
Abstract: NGC 7067 is a young open cluster located in the direction between the first and the second Galactic quadrants and close to the Perseus spiral arm. This makes it useful for studies of the nature of the Milky Way spiral arms. Strömgren photometry taken with the Wide Field Camera at the Isaac Newton Telescope allowed us to compute individual physical parameters for the observed stars and hence to derive the cluster's physical parameters. Spectra from the 1.93-m telescope at the Observatoire de Haute-Provence helped to check and improve the results. We obtained photometry for 1233 stars, individual physical parameters for 515 and spectra for 9 of them. The 139 selected cluster members lead to a cluster distance of 4.4 ± 0.4 kpc, with an age below log10 ( t ( yr )) = 7.3 and a present mass of 1260 ± 160 M⊙ . The morphology of the data reveals that the centre of the cluster is at (α, δ) = (21: 24: 13.69, +48: 00: 39.2) J2000, with a radius of 6.1 arcmin. Strömgren and spectroscopic data allowed us to improve the previous parameters available for the cluster in the literature.